Bankruptcy profile of the Islamic and conventional banks in Malaysia: a post-crisis period analysis - Jan, A. (2019)
This study identified that accounting for endogeneity in bankruptcy forecasting models have been widely over-sighted. This study used Altmanâs bankruptcy forecasting model to examine bankruptcy rates of the Islamic and conventional banks in Malaysia. Data for this study were collected from the post-crisis period 2009â2013. The results showed that the Islamic banks in Malaysia were more bankrupt as compared to the conventional banks. Hence, the claim of Islamic banks is in the stark contrast to the phenomena of being more shock-resilient to the financial crisis due to their Shariah compliance. Furthermore, the results of multiple regression analysis indicated that profitability possesses the highest explanatory power in reducing bankruptcy. However, the statistical tests Wu-Hausman and Durbin-Score identified profitability as an endogenous variable in Altmanâs model, which this study addressed with an instrumental variable. Thus, this study draws a conclusion that consideration of endogeneity in bankruptcy forecasting is essential, or else the results could be misleading. The results of the study lend credence to the researchers, policy-makers, and practitioners for accurate bankruptcy forecasting. Â© 2017, Springer Science+Business Media, LLC.